Temporary resolution of hemicrania continua following ipsilateral ear piercing. Issue 2 (27th September 2021) - Bryson, Alexander
Abstract : Background: Hemicrania continua is an uncommon subtype of trigeminal autonomic cephalgia that exhibits dramatic therapeutic response to indomethacin. Unfortunately, indomethacin is associated with a range of adverse effects, including neuropsychiatric complications, which limits its use in many patients. Although no other effective pharmacologic agents exist, there is emerging evidence for interventional treatments such as occipital nerve and vagus nerve stimulation, which may act by modulating neural activity within the trigeminovascular system. Case: We present a 30-year-old woman with long-standing refractory hemicrania continua who suffered adverse effects to indomethacin. She experienced temporary, but near-complete, symptom resolution following piercing of the crus of the ear helix ipsilateral to her headache, whereas contralateral piercing produced no benefit. Conclusions: To our knowledge, this case is the first to describe a therapeutic benefit following ear piercing in a patient with trigeminal autonomic cephalgia. We argue that symptom relief was obtained through a similar mechanism to occipital or vagus nerve stimulation.